Extensive theoretical/numerical comparative studies on H-2 and generalised H-2 norms in sampled-data systems - Kim, Jung Hoon; Hagiwara, Tomomichi (TAYLOR & FRANCIS LTD, 2017)
This paper is concerned with linear time-invariant (LTI) sampled-data systems (by which we mean sampled-data systems with LTI generalised plants and LTI controllers) and studies their H-2 norms from the viewpoint of impulse responses and generalised H-2 norms from the viewpoint of the induced norms from L-2 to L infinity. A new definition of the H-2 norm of LTI sampled-data systems is first introduced through a sort of intermediate standpoint of those for the existing two definitions. We then establish unified treatment of the three definitions of the H-2 norm through a matrix function G(tau) defined on the sampling interval [0, h). This paper next considers the generalised H-2 norms, in which two types of the L infinity norm of the output are considered as the temporal suwpremum magnitude under the spatial 2-norm and infinity-norm of a vector-valued function. We further give unified treatment of the generalised H2 norms through another matrix function F(theta) which is also defined on [0, h). Through a close connection between G(t) and F(theta), some theoretical relationships between the H-2 and generalised H2 norms are provided. Furthermore, appropriate extensions associated with the treatment of G(t) and F(theta) to the closed interval [0, h] are discussed to facilitate numerical computations and comparisons of the H-2 and generalised H-2 norms. Through theoretical and numerical studies, it is shown that the two generalised H-2 norms coincide with neither of the three H-2 norms of LTI sampled-data systems even though all the five definitions coincide with each other when single-output continuous-time LTI systems are considered as a special class of LTI sampled-data systems. To summarise, this paper clarifies that the five control performance measures are mutually relatedwith each other but they are also intrinsically different from each other.
Keywords: LINEAR PERIODIC-SYSTEMS; L-INFINITY; OPERATOR NORMS; H2; CONVOLUTION